Technology-driven Pedagogy in Primary Schools: Evaluating the impact of training and Professional Development on Educators (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The purpose of this research article is to conduct an in-depth analysis of the role that teacher training and professional development play in furthering the integration of educational technology in primary schools in India, with a particular emphasis on institutions that are governed by the government. For the purpose of this study, which was based exclusively on secondary data, a number of different training methods and policies at the national and state levels were investigated. In particular, the KITE and Hi-Tech School initiatives in Kerala were highlighted as noteworthy case studies. This study investigated the ways in which continual professional development affects the behaviour of teachers, their confidence, and the change of pedagogical practices in digital classrooms. A number of different training methods, such as in-person seminars, blended learning, online certification programs, and mentoring models, were examined in this article. The success of these training methods was evaluated based on how well they aligned with the reality of the classroom and relevant contextual requirements. The most important findings showed that although regulatory frameworks and digital platforms such as DIKSHA and NISHTHA have greatly increased access to training, there are still significant problems to be faced in terms of ensuring that training is of high quality, inclusive, and relevant to the area. It was discovered that the availability of follow-up assistance, leadership at the school level, and access to digital resources were all directly related to the effectiveness of training projects. The experience of Kerala shown that when professional development is localised, supported by policy, and accompanied by infrastructure support, it has the potential to result in significant increases in teacher engagement and the utilisation of technology in the classroom. On the other hand, the discrepancies that exist between rural and urban schools, as well as the uneven execution of these initiatives, continue to restrict their reach and their potential to be sustainable. The research highlighted the need of developing training programs that are research-informed, context-sensitive, and focused on the needs of the community. These programs should also include ongoing mentorship and community engagement. In order to develop teacher capacity-building systems, it is vital to take a collaborative strategy that involves government authorities, non-governmental organisations, and EdTech companies. In the end, the study came to the conclusion that it is vital to empower teachers via inclusive and long-term professional development in order to both revolutionise primary education and ensure that technology is used meaningfully in order to improve learning outcomes.